2021
DOI: 10.1177/1461444821993038
|View full text |Cite
|
Sign up to set email alerts
|

Snapchat lenses and body image concerns

Abstract: Snapchat allows users to apply lenses to photographic content, with these lenses often enhancing physical appearance. This may lead users to adopt unrealistic ideals of physical appearance. In a two-part study with college students, this investigation explored associations between general use of Snapchat lenses and body image concerns, and experimentally examined how taking selfies with Snapchat lenses influences appearance satisfaction. Taking more photos using Snapchat lenses, in general, was associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Thus, current research suggests that taking and especially editing, but not posting, selfies may be harmful for body image. This conclusion seems to apply across genders (except [23]), even though boys/men spend considerably less time taking and editing selfies than girls/women [20,24,27].…”
Section: Creating Editing and Posting Self-imagesmentioning
confidence: 82%
See 3 more Smart Citations
“…Thus, current research suggests that taking and especially editing, but not posting, selfies may be harmful for body image. This conclusion seems to apply across genders (except [23]), even though boys/men spend considerably less time taking and editing selfies than girls/women [20,24,27].…”
Section: Creating Editing and Posting Self-imagesmentioning
confidence: 82%
“…Cross-sectional studies have largely supported this reasoning and shown consistent correlations between selfie-behaviors and body image disturbance [13,20,[22][23][24]. However, it is important to distinguish between the different selfie behaviors.…”
Section: Creating Editing and Posting Self-imagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have included SM variables of Facebook, Pinterest, Reddit, TikTok, and YouTube in conglomerate with results expressed in total SM usage and time ( 69 ). Other studies have collected robust data on the influence of solely Instagram and Snapchat contributing to BII in both males and females ( 70 72 ). In comparison, our data presents novel findings across many different SM platforms (Instagram, Facebook, Snapchat, TikTok, Pinterest, YouTube, Reddit, and Twitter) by exploring the relationship of BII and SM through assessment of specific SM platforms used by males vs. females and their individual influences on BII.…”
Section: Discussionmentioning
confidence: 99%